Kepengaturan dan Penolakan Relokasi: Kasus Warga Watugajah Pascabencana Gunung Merapi Tahun 2011-2013 - Lubabun Ni’am (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2014)
After the 2010 Mount Merapi eruption, the people of Watugajah Village, Magelang District, Central Java Province, were conducted to relocate from their hometown. The resettlement programme was implemented as part of post-disaster governmentality means with birocratic rationality on disaster-prone zone. Governmentality is “an att empt to regulate people through calculated means” (Li, 2007: 275); “the techniques and procedures that undertakes to conduct individuals throughout their lives by placing them under the authority of a guide responsible for what they do and for what happens to them” (Foucault, 2003). Based on an empirical research in Watugajah and several secondary data from various sources (news and programme handbook), this article examines a research question: how the contestation among the actors in Watugajah happened to the case of the people’s denial of the relocation in the context of Mount Merapi post-disaster? This article shows an inquiry that the denial is not a part of an antipathy to the governmental authority. Instead, people show both their self defence positioning to get the bett er life based on their own reason as well as their tactical positioning to be head-to-head with the programmes, aids, and the policies derived from various sides.